2018
DOI: 10.4025/jphyseduc.v29i1.2936
|View full text |Cite
|
Sign up to set email alerts
|

Controle Postural De Atletas Com Diferentes Graus De Deficiência Visual

Abstract: O objetivo do estudo foi descrever o controle postural na posição ereta semiestática de atletas com diferentes graus de deficiência visual e verificar se existem diferenças de acordo com a modalidade esportiva praticada. Participaram deste estudo seccional 22 atletas com perda total da visão (classificação funcional B1) e 17 com baixa visão (classificação funcional B2 e B3) das modalidades judô (n=17), goalball (n=12) e futebol de cinco (n=10). O controle postural foi investigado utilizando uma plataforma de f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…In this vein, the differences found in postural control in a force platform in para-judokas seem to be associated with the degree of loss of vision and specificities of each sport modality. Hence, goalball athletes oscillated less and presented smaller displacement velocity than para-judokas 26 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this vein, the differences found in postural control in a force platform in para-judokas seem to be associated with the degree of loss of vision and specificities of each sport modality. Hence, goalball athletes oscillated less and presented smaller displacement velocity than para-judokas 26 …”
Section: Resultsmentioning
confidence: 94%
“…Hence, goalball athletes oscillated less and presented smaller displacement velocity than para-judokas. 26 In para-judokas, nonathletes with VI, and sighted nonathletes, postural control performance was qualitatively compared and did not differ among the three groups. 27 These authors concluded that the Balance Error Scoring System test may not be sensitive to group-related differences in the quantitative kinematics of postural control.…”
Section: Physical Fitnessmentioning
confidence: 99%
“…Acquired visual deficits tend to have a more pronounced effect on postural control than congenital ones [ 29 ]. Furthermore, an exploration of visually impaired athletes across diverse sports revealed that postural control disparities were linked to the extent of visual loss and sports-specific modalities [ 30 ]. The cohort in our study predominantly comprised individuals with mild-to-moderate acquired visual deficits.…”
Section: Discussionmentioning
confidence: 99%
“…This system is a personal complex sensory system. Vision, hearing, joint position sense, and other sensory organs play an important role in performing sports-specific skills [ 3 , 4 ]. When the reception of visual stimuli is limited, the data flow decreases [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%